Emptied lands : a legal geography of Bedouin rights in the Negev - Kedar, Alexandre; Amara, Ahmad; Yiftachel, Oren, 1956- (Stanford, California : Stanford University Press, 2018)
Since its establishment, the Jewish State has devoted major efforts to secure control over the land of Israel. One example is the protracted legal and territorial strife between the Israeli state and its indigenous Bedouin citizens over traditional tribal land in the Negev in southern Israel. 'Emptied Lands' investigates this multifaceted land dispute, placing it in historical, legal, geographical, and comparative perspective. The authors provide the first legal geographic analysis of the 'Dead Negev Doctrine,' which has been used by Israel to dispossess Bedouin inhabitants and Judaize the southern half of the country. Through crafty use of Ottoman and British laws, particularly the concept of 'dead land,' Israel has constructed its own version of terra nullius. Yet, the indigenous property system still functions, creating an ongoing resistance to the Jewish state.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 9, 2018).
Keywords: Bedouins -- Legal status, laws, etc. -- Israel -- Negev; Bedouins -- Land tenure -- Israel -- Negev; Land tenure -- Law and legislation -- Israel -- Negev; Law; Indigenous peoples; Jurisprudence & general issues; Laws of specific jurisdictions & specific areas of law